Biomechanical Effects of Different Spacing Distributions Between the Cemented Superior Boundary and Surgical Vertebral Superior Endplates After Percutaneous Vertebroplasty for Osteoporotic Vertebral Compression Fractures: A Three‐Dimensional Finite Element Analysis - Xiao Meng; Chengqiang Zhou; Yifeng Liao; Haibin Zhou; Hua Li; Jiayuan Liu; Xuebin Tang; Yunqing Wang (Orthopaedic Surgery)
ABSTRACT Objective Patients with osteoporotic vertebral compression fractures (OVCF) treated with vertebroplasty (PVP) are experiencing an increasing number of problems such as pain recurrence, mainly due to recompression fractures of the operated vertebral body within a certain period of time after the operation, which is closely related to the distribution of intraoperative bone cement. The aim of this study is to investigate the effect of different spacing distributions between the upper boundary of the cement and the upper endplate of the operated vertebra on the biomechanics of the operated vertebra after percutaneous vertebroplasty for OVCF using finite element analysis (FEA). Methods One patient with L1 vertebral body OVCF was selected, and computed tomography (CT) of the thoracolumbar segment was performed. The CT data were extracted to establish an FEA model of the T12–L2 vertebral bodies. Bone cement was injected into the L1 vertebral body. Based on the spacing between the upper boundary of the bone cement and the vertebral body's upper endplates, the model vertebrae were divided into 0, 2, 4, and 6 mm spacing groups, and the human body's upright, flexion–extension, lateral flexion, and rotational positions were simulated. The biomechanical effects of different spacing distributions on the postoperative L1 vertebral body and the injected bone cement were evaluated. Results In this paper, we found that the Von Mises stress of the L1 vertebrae was the smallest when the spacing between the upper boundary of the bone cement and the vertebral body's upper endplates was 0 mm. The larger the spacing in a certain range between the upper boundary of the bone cement and the vertebral body's upper endplates, the greater the Von Mises stress of the L1 vertebrae. However, in the stress comparison of the injected bone cement, the Von Mises stress of the bone cement was greatest when the spacing between the upper boundary of the bone cement and the upper endplate of the vertebral body was 0 mm; the larger the spacing, the smaller the Von Mises stress. Conclusion When the contact spacing between the upper boundary of the bone cement and the upper endplate of the vertebral body is 0 mm, it can effectively eliminate and transfer the pressure caused by the load, thus reducing the stress on the cancellous bone and further reducing the risk of vertebral refracture after surgery.